PUBLIC INVESTMENT AND OUTPUT PERFORMANCE IN NIGERIA (2014)
In Nigeria, there is a divergence between growth in public investment and output performance. The average annual growth rate of public investment (PI) was 3.6% in 1970-74, increased significantly to 20.5% during 1980-84 and declined steadily to 9.0% and 4.2% in 1990-94 and 2005-10, respectively. Over the same periods, the average output growth fluctuated considerably between 2.5% and 6.2%. While there are studies on the impact of PI on output, little attention has been devoted to the channels through which PI affects output performance. This study, therefore, examined the channels and effects of PI on aggregate and sectoral output in Nigeria during 1970-2010. A macro-econometric model derived from Keynes’ income-expenditure framework was employed. The model was disaggregated into demand and supply sides in order to trace the direct and indirect effects of PI on aggregate and sectoral output. Agriculture, manufacturing, services, wholesale and retail, mining and quarrying, crude petroleum, building and construction constituted the supply side. Household consumption, domestic investment and external trade represented the demand side. The direct effect was assessed using the magnitude of PI multiplier coefficients on aggregate and sectoral output. The indirect effect of PI on demand side was evaluated with marginal propensity to consume, accelerator coefficient and import multiplier, respectively. Three-stage least squares estimation technique that took into consideration cross error correlation and simultaneity bias was used. Tests of the model’s reliability were carried out using root mean square error, proportion inequality and graphical representation of both actual and simulated values of the endogenous variables. Data were collected from Central Bank of Nigeria’s Statistical Bulletins and National Bureau of Statistics’ Annual Abstracts. All the estimates were validated at p≤0.05. There were marginal direct effects of PI on aggregate and some sectoral output, while the indirect effects were significant. Public investment multiplier for aggregate output was 0.21 and significant. The small value of the multiplier was attributed to low marginal productivity, inefficient and relative decline of public investment. Wholesale and retail trade had the largest significant multiplier of 0.31, followed by building and construction (0.21), manufacturing (0.17), agriculture (0.16) and mining and quarrying (0.11). The multipliers of public investment in services (0.13) and crude petroleum (0.03) sectors were insignificant. The values of marginal propensity to consume (0.68), the accelerator coefficient (0.49) and the import multiplier (0.86) were significant. This suggested that a ₦1 increase in PI would increase household consumption, domestic investment and external trade by 68k, 49k and 86k, respectively. The graphical representation indicated that the actual and simulated series are close and the turning points of the actual series were well tracked by the simulated values. Public investment exerted marginal influence on aggregate output. The significant effect of the indirect channel with the import multiplier being the most pronounced was evident. Therefore, in order to accelerate aggregate and sectoral output growth, there should be increased emphasis on productivity and efficiency of public investment.